Implementasi Nilai-Nilai Persatuan Dalam KomunitasMusik "Orang Indonesia Solo Raya" - , Riyanto; , Drs. Hj. Sri Gunarsi, SH, MH (2017)
This study aims to mendieskripsikan implementation of the values of unity within the music community on community " Orang Indonesia Solo Raya", obstacles faced, and the solutions provided. This study used a qualitative research with case study strategy. Techniques of data collection is done by observation, interviews, dandokumentasi. Test the validity of the data by triangulation of data sources and teknikpengumpulan data. Analysis of the data using interactive analysis techniques through data collection, data reduction, display data and conclusion The results showed that the implementation of the values of unity within the music community is based on the same feeling of togetherness. Ie on the basis of the same feeling among members to other people or society. Both the nature of human nature as social beings, are some of the activities concerning the organization of the humanitarian sector that is useful foster a sense of unity. All three dependency between people from each other, ie empowerment program held for members who have not worked. Fourth their mental boost as high as low, which means not applicable caste in organizations that set apart the management structure which is required. The fifth of the urge to help the distress of others, namely both in terms of social movements from economic crisis center their share of sales revenue from merchaindaise. Obstacles encountered during the preparation of the agenda is routine activity held. The solution is fleksibelnya meeting time to anticipate the presence of a majority of members.